2002
DOI: 10.1086/338242
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Gene Interaction in Asthma: IL4RA and IL13 in a Dutch Population with Asthma

Abstract: Asthma is a common respiratory disease that is characterized by variable airways obstruction caused by acute and chronic bronchial inflammation; associated phenotypes include bronchial hyperresponsiveness (BHR), elevated total serum immunoglobulin E (IgE) levels, and skin tests positive to common allergens. Binding of interleukin-13 (IL13) or interleukin-4 (IL4) to the IL4 receptor (IL4R) induces the initial response for Th2 lymphocyte polarization. Both IL13 and IL4 are produced by Th2 cells and are capable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
196
5
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(221 citation statements)
references
References 30 publications
16
196
5
4
Order By: Relevance
“…Although, the results of these linkage mappings varied across studies and across racial and ethnic groups, regions 5q and 13q are two of the few most frequently reproduced regions in these studies Ober et al 1998;Ober et al 2000;Wiltshire et al 1998;Xu et al 2000). It is interesting to note that these regions contain the asthma candidate genes IL4, IL13, and TGFβ, which have been studied extensively (Bartram and Speer 2004;Basehore et al 2004;Battle 2007;CamorettiMercado and Solway 2005;Howard et al 2002;Li et al 2007;Marsh et al 1994). In addition, these regions contain several new potential asthma candidate genes including IL3, IL5, IL9, SMAD5, IRF1, FBN2 and SMAD9 that warrant further investigation.…”
Section: Discussionmentioning
confidence: 95%
“…Although, the results of these linkage mappings varied across studies and across racial and ethnic groups, regions 5q and 13q are two of the few most frequently reproduced regions in these studies Ober et al 1998;Ober et al 2000;Wiltshire et al 1998;Xu et al 2000). It is interesting to note that these regions contain the asthma candidate genes IL4, IL13, and TGFβ, which have been studied extensively (Bartram and Speer 2004;Basehore et al 2004;Battle 2007;CamorettiMercado and Solway 2005;Howard et al 2002;Li et al 2007;Marsh et al 1994). In addition, these regions contain several new potential asthma candidate genes including IL3, IL5, IL9, SMAD5, IRF1, FBN2 and SMAD9 that warrant further investigation.…”
Section: Discussionmentioning
confidence: 95%
“…4 The IL13 gene encompasses 2938 bp and includes four exons, 56 bp of 5 0 UTR and 828 bp of 3 0 UTR ( Figure 1). Previous studies [6][7][8][9][10][11] and single-nucleotide polymorphism (SNP) discovery initiatives such as the University of Washington-Fred Hutchinson Cancer Research Center Variation Discovery Resource (http://pga.gs.washington.edu/) and SNP500Cancer (http://snp500cancer.nci.-nih.gov/) have identified 32 SNPs in the IL13 gene and its promoter region in European, European-American, Chinese, Japanese, African American and African samples. These include two SNPs in the promoter region and a single nonsynonymous substitution (2043G4A, Arg130Gln), located in exon 4.…”
Section: Introductionmentioning
confidence: 99%
“…These include two SNPs in the promoter region and a single nonsynonymous substitution (2043G4A, Arg130Gln), located in exon 4. Epidemiological studies in different populations have shown an association of the À1111T allele in the promoter region, 8,9,12 or of the Gln130 allele, 6,7,12 with different asthma-related disorders and proximal risk phenotypes, such as serum IL-13 and IgE levels. Moreover, Hoerauf et al 13 have identified an association between the Gln130 allele and sowda, an immunological hyper-reactive form of onchocerciasis.…”
Section: Introductionmentioning
confidence: 99%
“…26 50 analyzed IL-4R gene polymorphisms in families in Germany and did not find evidence that the ILe50VaL is the main responsible for susceptibility to allergy, suggesting that other IL-4R polymorphisms are associated with asthma and atopy.…”
Section: Discussionmentioning
confidence: 99%